P2X7 Blockade Attenuates Murine Lupus Nephritis by Inhibiting Activation of the NLRP3/ASC/Caspase 1 Pathway. Issue 12 (27th November 2013) - Zhao, Jijun; Wang, Hongyue; Dai, Chao; Wang, Hongyang; Zhang, Hui; Huang, Yuefang; Wang, Shuang; Gaskin, Felicia; Yang, Niansheng; Man Fu, Shu
Abstract : Objective: The NLRP3 inflammasome plays key roles in inflammation and autoimmunity, and purinergic receptor P2X7 has been proposed to be upstream of NLRP3 activation. The aim of the present study, using murine models, was to investigate whether the P2X7 /NLRP3 inflammasome pathway contributes to the pathogenesis of lupus nephritis (LN). Methods: MRL/ lpr mice were treated with the selective P2X7 antagonist brilliant blue G (BBG) for 8 weeks. Following treatment, the severity of renal lesions, production of anti–double‐stranded DNA (anti‐dsDNA) antibodies, rate of survival, activation of the NLRP3/ASC/caspase 1 inflammasome pathway, and ratio of Th17 cells to Treg cells were evaluated. P2X7 ‐targeted small interfering RNA (siRNA) was also used for in vivo intervention. Similar evaluations were carried out in NZM2328 mice, a model of LN in which the disease was accelerated by administration of adenovirus‐expressing interferon‐α (AdIFNα). Results: Significant up‐regulation of P2X7 /NLRP3 inflammasome signaling molecules was detected in the kidneys of MLR/ lpr mice as compared with normal control mice. Blockade of P2X7 activation by BBG suppressed NLRP3/ASC/caspase 1 assembly and the subsequent release of interleukin‐1β (IL‐1β), resulting in a significant reduction in the severity of nephritis and circulating anti‐dsDNA antibodies. The lifespan of the treated mice was significantly prolonged. BBG treatment reduced the serum levels of IL‐1β and IL‐17 and the Th17:Treg cell ratio. Similar results were obtained by specific siRNA silencing of P2X7 in vivo. The effectiveness of BBG treatment in modulating LN was confirmed in NZM2328 mice with AdIFNα‐accelerated disease. Conclusion: Activation of the P2X7 signaling pathway accelerates murine LN by activating the NLRP3/ASC/caspase 1 inflammasome, resulting in increased IL‐1β production and enhanced Th17 cell polarization. Thus, targeting of the P2X7 /NLRP3 pathway should be considered as a novel therapeutic strategy in patients with lupus.